Empowering social protection system. the role of government and a way forward / Suhaimi Abdul Samad - Abdul Samad, Suhaimi (Universiti Teknologi MARA, 2019)
Ageing population, unstable labour market and economic condition, changing in job nature, rise of the informal sector, and emergence of epidemic diseases have resulting the need for a dynamic social protection system. The less developed and developing countries are those who affected with these challenges and they are urged to provide adequate and comprehensive protection especially for the vulnerable groups. The undermining of socio and economic capability in a country requires better attention from the government in providing protection to ensure the public especially the vulnerable groups will not fall through the safety net. Inevitably, the role for social protection relies heavily on the government as a policy formulator and legislator, as a policy implementer and administrator, and as a mediator. This is emphasized by the International Labour Organization that the government should play a significant role in providing adequate or at least sufficient social protection to the public. Malaysia is no exception. To make evident this statement, several evidences are presented in this paper by referring to informants, published data, and information from secondary sources such as scholarly articles and journals, data from the web and newspapers. Some recommendations have also outlined the comprehensive roles of the government in empowering the social protection in Malaysia.